Bullying and self-esteem in adolescents from public schools - Camila C. Brito; Marluce T. Oliveira (Brazilian Society of Pediatrics, 2013)
Objectives: to perform a situational analysis of bullying and self-esteem in municipal school units, by estimating the prevalence of bullying, according to gender, age, and role in bullying situations; and to identify the level of self-esteem of students by gender and role in bullying situations and correlate with the involvement in bullying situations. Methods: this was a cross-sectional study with 237 students in the ninth grade of middle school from public schools participating in the School Health Program in the city of Olinda (PE). The questionnaire used in the study was divided into three blocks: a sociodemographic block; a block on bullying, validated by Freire, Simão, and Ferreira (2006); and a block to assess self-esteem, by Rosenberg (1989). Results: the prevalence of bullying was 67.5%. The study population consisted of adolescents, mostly female (56.4%), aged 15-19 years (51.3%), of black ethnicity (69.1%). Most students lived with four or more people (79.7%) in their family-owned homes (83.8%), which had five or more rooms (79.1%). Observing bullying or being bullied were the most often reported situations (59.9% and 48.9%, respectively); when the roles of bullying are associated with self-esteem in relation to gender, it was observed that in the group of victims/aggressors and aggressors (p = 0.006 and 0.044, respectively), males had higher statistically significant self-esteem scores when compared to females. Conclusion: the findings indicate a large number of students involved in the several roles of bullying, identifying an association between these characteristics and sex/gender and self-esteem of those involved. The present study has identified the need for further studies on the nature of the event.